(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the epidemiological and vaccination profile of suspected measles cases, establishing the relationship between vaccination, symptoms, and hospital admission in municipalities in the Northern health region of Minas Gerais. Methodology: The North of Minas Gerais health macro-region has 1,125,986 inhabitants and 54 municipalities. A survey was carried out on the distribution of the number of measles cases in all municipalities in the North macro-region of Minas Gerais, from 2016 to 2021, based on secondary data obtained from the Notifiable Diseases Information System. Reported cases of 140 individuals with suspected measles were analyzed. The selected variables refer to factors of a sociodemographic and clinical nature, vaccination coverage, hospitalization, confirmation of suspicion and the number of cases per year. Results: The study identified that the number of suspected measles cases in the period was 140, corresponding to 81% of the total reported febrile exanthematous diseases, against 31 notifications for rubella (19%), in the territory covered by the health macro-region. North of Minas Gerais. As for vaccination, 97 people were vaccinated and 33 were not vaccinated, and it was not possible to establish a relationship between vaccination/symptomology and vaccination/hospitalization. Final considerations: Considering that vaccination is the main effective measles control measure, when 95% coverage is reached. further studies on measles are needed, in addition to reflection by public authorities, health professionals and the population on the importance of vaccination campaigns for greater adherence, including prevention of imported cases and disease control.